Patient empowerment through provision of a mobile application for medication reconciliation: a proof of concept study. Issue 4 (28th September 2016) - Werumeus Buning, Annabel; Klopotowska, Joanna E; Duyvendak, Michiel; Engelen, Lucien JLPG; Arts, Joris
Abstract : Background: The operationalisation of medication reconciliation in daily practice is challenging, due to among others, insufficient interoperability of computer systems and high implementation costs. Involving patients in the medication reconciliation process by using information technology could potentially overcome these difficulties and reduce preventable patient harm accordingly. Objective: The MyMedication app (MMa) is a mobile application developed to help patients keep their medication list up to date. This study aims to investigate the usability and reliability of MMa for medication reconciliation at care transitions. Method: A random convenience sample of 17 patients was recruited during August–September 2014 at the Antonius Hospital in Sneek and Emmeloord, the Netherlands. Patients were asked to compile their medication list in MMa prior to their elective surgery. At admission, the medication list in MMa was compared with the medication list compiled by a pharmacy practitioner and the number of medication discrepancies per patient quantified. Acceptance and usability was assessed using a validated System Usability Scale (SUS) questionnaire and interviews. Results: The mean number of medication discrepancies between the medication list in MMa and the list compiled by the standard procedure was 2.5 per patient. When discrepancies caused by technical errors in the MMa were excluded, only a mean number of 1.2 discrepancies per patient remained. MMa SUS indicated good usability (68/100). Conclusions: The results of this study show that patients are positive about the use of the MMa and some feel even more involved in their medication treatment. The use of MMa for medication reconciliation at care transition shows potential as tool to improve patient safety and to reduce healthcare costs.